(untitled) (Central Medical College Journal, 2022)
Background: E. coli is found to be the commonest cause of Urinary Tract Infection (UTI). However, E. coli antibiotic resistance has escalated over the past many years. To observe the possible uropathogen from suspected UTI male outdoor patient, different pathogenic bacteria isolated and identified from urine sample by culture and biochemical tests. Out of 200 urine samples, 160 (80.00%) yielded significant bacterial growth. Among them E. coli was the most predominant bacteria 82 (51.25%) followed by Klebsiella 30 (18.75%), Pseudomonas 14 (8.75%), Proteus 10 (6.25%) and different Gram positive bacteria 10 (6.25%). Only antibiotic susceptibility test of E. coli was done. All (100%) E. coli were sensitive to imipenem and colistin sulphate and 100% resistant to ciorofloxacin. In conclusion, it can be said that antibiotic resistance against commonly using antibiotics is an alarming sign for us to treat the outdoor patients. Central Medical College Journal Vol 5 No 1 Jan 2021 PP 47-50